Carbon monoxide poisoning is associated with increased risk of migraine in the long term: a nationwide population-based cohort study - Heewon Hwang; Solam Lee; Yeon-Woo Heo; Woo-Seok Ha; Kyung Min Kim; Yong Sung Cha; Yong Sung Cha (Frontiers in Toxicology)
ObjectiveCarbon monoxide poisoning can cause migraine-like attacks. However, the association between carbon monoxide poisoning and the risk of migraine has not been thoroughly studied. This study aimed to investigate the long-term risk of migraine in patients with carbon monoxide poisoning.MethodsThis nationwide, population-based cohort study was conducted using the administrative database of the National Health Insurance Service of Korea from 2002 to 2021. Patients with carbon monoxide poisoning with at least one visit documented according to the International Classification of Diseases, 10th Revision code T58 were included. Patients were only included if they had the same diagnostic code at two or more outpatient clinic visits. The primary outcome of this study was the incidence of migraine after carbon monoxide poisoning.ResultsThe overall risk of migraine was higher in the carbon monoxide poisoning group regardless of age, sex, or use of hyperbaric oxygen therapy (adjusted hazard ratio, 1.37; 95% confidence interval, 1.28–1.48). The carbon monoxide poisoning group had a persistently higher cumulative incidence of migraine during the observation period than the control group.ConclusionCarbon monoxide poisoning was associated with an increased overall risk of developing migraine during long-term follow-up.